Mental well-being: An important outcome for mental health services?. (September 2015) - de Cates, Angharad; Stranges, Saverio; Blake, Amy; Weich, Scott
Summary: Mental well-being is being used as an outcome measure in mental health services. The recent Chief Medical Officer's (CMO's) report raised questions about mental well-being in people with mental illness, including how to measure it. We discuss whether mental well-being has prognostic significance or other utility in this context.